Prospects for in vivo NMR methods in xenobiotic research in plants - Ratcliffe, R; Roscher, A (Kluwer Academic Publishers, 1998)
The application of non-invasive nuclear magnetic resonance (NMR) methods in xenobiotic research is reviewed in relation to: (i) the characterisation of the effects of xenobiotics on the metabolism of plants and plant cell suspensions; (ii) the direct detection of xenobiotics and their degradation products in vivo; and (iii) the spatial localisation of xenobiotics and their derivatives at the subcellular and tissue levels. Novel information has been generated by in vivo NMR studies of both agrochemicals and heavy metals, but a lack of generality in the methods makes it difficult to extrapolate from one successful application to the next. In vivo NMR spectroscopy is shown to be informative when a xenobiotic perturbs metabolic pathways that are accessible to the technique, and it is useful for probing the partitioning of paramagnetic metal ions between the cytoplasm and the vacuole. The successful application of 19F NMR to the analysis of plant tissue extracts also suggests that in vivo 19F NMR spectroscopy may have a role in biotransformation studies of fluorinated xenobiotics. In contrast NMR imaging techniques have been little used for xenobiotic research in plants, and while the method has been shown to be capable of monitoring the uptake and translocation of paramagnetic ions in plants, the potential use of high resolution 1H and 19F NMR imaging for mapping agrochemicals in tissues is still in its infancy.